Expression of the type 2 receptor for cysteinyl leukotrienes (CysLT2R) by human mast cells: Functional distinction from CysLT1R - Mellor, Elizabeth A. (National Academy of Sciences, 2003)
Cysteinyl leukotrienes (cysLTs) mediate vascular leakage and bronchoconstriction through the smooth muscle-associated CysLT type 1 receptor (CysLT1R), one of at least two loosely homologous cysLT-binding G protein-coupled receptors. We previously reported that CysLT1R is expressed by cultured human mast cells (hMCs), and that priming these cells with IL-4 enhances their sensitivity to calcium flux and cytokine generation in response to cys-LTs and the nucleotide ligand, uridine diphosphate (UDP), without increasing their surface expression of CysLT1R. We now report that hMCs express the type 2 receptor for cysLTs (CysLT2R) as well, and that the amount of surface CysLT2R protein increases in response to priming with IL-4. The selective function of CysLT2R was evident based on uninhibited IL-8 secretion by IL-4-primed hMCs stimulated with cys-LTs or UDP in the presence of the selective CysLT1R antagonist MK571. MK571 did inhibit IL-5 generation, calcium flux, and phosphorylation of extracellular signal-regulated kinase. IL-8 secretion was inhibited by pertussis toxin and a selective p38 kinase inhibitor, SB203580. The CysLT2 response may permit the cys-LTs and nucleotides generated in infection and tissue injury to elicit IL-8 generation by hMCs, potentially leading to neutrophilic infiltration, a characteristic of aerosol challenge-induced late-phase responses and of sudden death associated with asthma.